MERCOSUR: Another failed move towards regional integration? - Heinz Gert Preuße (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2000)
In this paper the present challenges of consolidation and deeper integration of Mercosur will be discussed, in order to shed some light on the nature of the problems, that might be responsible for the present slow down of the speed of integration. In the second chapter I shall outline the concept of Mercosur. In the third chapter the formation of Mercosur will be discussed and in the fourth chapter I shall evaluate the future prospects of Mercosur.
urn:nbn:de:bsz:21-opus-19572
Keywords: 330; Handelsregionalismus; Wirtschaftsunion; MERCOSUR-Staaten